(untitled) (Damascus University Journal for engineering sciences, 2024)
Mathematical modeling has become a critical tool for long-term water treatment management, particularly for simulating complex biological processes. This study focuses on modeling and simulating a sewage treatment plant in Al- zabadani, in which sewage is treated by the extended aeration activated sludge method. This research aims to determine the design values of the factors affecting the biological treatment process with extended aeration of wastewater in the Al- zabadani plant. Such as intensity of aeration and control of the amount of excess sludge and sludge returned. GPS-X program was used to simulate the operation of the plant and check its performance under different operating conditions. Multiple samples were taken from 20/1/2020 to 14/9/2021 and experiments were conducted on them. Four scenarios were applied using the GPS-X program to improve the operational reality of the plant, and the results showed the significant impact of the mentioned factors This is through a clear improvement in the station’s work in the winter, as the COD concentration decreased from (72-40) mg/l, the BOD concentration from (20-45) mg/l, and the ammonia concentration from (32-9 mg/l). In summer, the COD concentration decreased from (46-39) mg/l, the BOD concentration from (15-20.5) mg/l, and the ammonia concentration from (1-25 mg/l).